If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -36x + -6x + -24 = -12 Reorder the terms: 12 + -24 + -36x + -6x = -12 Combine like terms: 12 + -24 = -12 -12 + -36x + -6x = -12 Combine like terms: -36x + -6x = -42x -12 + -42x = -12 Add '12' to each side of the equation. -12 + 12 + -42x = -12 + 12 Combine like terms: -12 + 12 = 0 0 + -42x = -12 + 12 -42x = -12 + 12 Combine like terms: -12 + 12 = 0 -42x = 0 Solving -42x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-42'. x = 0 Simplifying x = 0
| 5(9x-5)+12x= | | g(2)=7x-4 | | 2x+3y=4z-3xy | | 5a+35-12a-3=12-12a | | 2+3(-8n+6)=116 | | 125+15m=800 | | 10x+90=8x | | 3+(6x+4)=9 | | 2x+x-250=2858 | | 3(3Y-5)Y=-15 | | 8y-5x=27 | | 3a+15=3(a+5) | | 7=8(x+4)-2x | | 13-8b=-4b+5 | | 460g+g=11g | | 4-3(2-y)=y-2(3y-7) | | 18x+(-8+23)=5x(3+4) | | x-3x=60 | | -75+W=0 | | 1.2a+1.2a=a+1 | | x+2x=1.30 | | 4y+14+3y=5y-2 | | 2x-3=5c-1 | | 1+n=7+n+6+2n | | y+5.7=-3.8 | | -5(-3+x)=-5(3+3x) | | 4a-9=3.5-9 | | 8.9-w=10.3 | | 20m=0.4 | | y=(3x+10)-(-5x+200) | | -5m=-8-6m | | 9p^5q^3= |